Effects of wheat bran replacement with pomegranate seed pulp on rumen fermentation, gas production, methanogen and protozoa populations of camel and goat rumen using competitive PCR technique: An in vitro study - Sanaz Jaberi Darmiyan; Mohammad Bagher Montazer Torbati; Mohammad Ramin; Seyed Ehsan Ghiasi (Veterinary Medicine and Science, 2023)
Abstract Background Microbial populations in the rumen play an essential role in the degradation of Cellulosic dietary components and in providing nutrients to the host animal. Objective This study aims to detect the effect of pomegranate seed pulp (PSP) on rumen fermentation, digestibility and methanogens and the protozoa population (by competitive polymerase chain reaction [PCR]) of the camel and goat rumen fluid. Materials and methods PSP was added to the experimental treatments and replaced by wheat bran (0%, 5% and 10%). Rumen fluid was collected from three goats and two camels according to the similarity of sex, breed, origin and time and used for three gas production studies. DNA extraction was performed by the RBB + c method, the ImageJ programme calculated band intensities (target and competing DNA), and line gradients were plotted based on the number of copies and intensity. Results Our result showed that diets did not significantly affect the methanogen and protozoa population. Animal species affected microbial populations so that both populations in camels were less than goats. The production of gas and volatile fatty acids was not affected by diets. These two parameters and NH3 concentration and methane production in goats were higher than in camel. The pH of digested dry matter and microbial protein in camels was higher than in goats. Conclusions Therefore, the competitive PCR technique is an effective method for enumerating rumen microbiota. This supplementation can be considered a strategy to achieve performance and environmental benefits.